2010
DOI: 10.1152/ajpendo.00115.2010
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation activates the nuclear factor-κB regulatory pathway in adipose tissue

Abstract: Adipose tissue (AT) is a store of energy but also an endocrine organ with the capacity to produce and release proinflammatory mediators into the circulation. The mechanism that may trigger human AT inflammation on a cellular level still remains largely unknown. The aim of this study was to investigate whether an acute systemic inflammation increases AT inflammatory activity, focused on innate immunity. Open heart surgery results in an extensive acute systemic inflammation. Therefore, we investigated the in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
2
18
0
1
Order By: Relevance
“…Inflammatory mediators from surgery trauma, such as IL6, are associated with thrombocytosis [31], and work performed by our group and others has shown that after CABG there is a systemic increase in plasma IL6 [25,27]. Our results showed an increase in CRP levels and numbers of circulating leukocytes, both of which confirm a strong inflammatory reaction.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Inflammatory mediators from surgery trauma, such as IL6, are associated with thrombocytosis [31], and work performed by our group and others has shown that after CABG there is a systemic increase in plasma IL6 [25,27]. Our results showed an increase in CRP levels and numbers of circulating leukocytes, both of which confirm a strong inflammatory reaction.…”
Section: Discussionsupporting
confidence: 78%
“…CABG surgery represents one of the strongest models of inflammation in humans and results in extensive acute inflammation. After CABG there is a huge increase in gene expression and plasma protein levels of inflammatory mediators such as tumor necrosis factor, interleukin (IL) 6 and IL1 [25–27]. This extreme inflammatory response might contribute to a number of post‐surgery complications, including thrombus formation and MI [9].…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated a novel mechanism of adipose tissue inflammation involving the FFA chaperone protein fetuin-A (32). We hypothesized that adipose tissue inflammatory pathways could be triggered directly by fructose-induced systemic inflammation (11) or indirectly by fetuin-A activation of inflammatory pathways in adipose tissue (15). We measured several genes in adipose tissue known to be involved in the inflammatory process and quantified and characterized the activation state of immune cell populations isolated from the SVF in a comprehensive effort to detect any differential effect of the beverages on adipose tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…First, high fructose consumption, even under short-term isocaloric conditions, promotes the translocation of microbial material from the gut lumen to the portal circulation in rodents, thereby triggering low-grade hepatic and systemic inflammation (7,10). Because systemic inflammation can trigger the activation of inflammatory pathways in adipose tissue (11), we hypothesized that hepatic and systemic inflammation triggered by increased intestinal permeability and endotoxinemia may also result in changes in adipose tissue inflammation. Second, even under isocaloric conditions, substituting liquid fructose in place of solid carbohydrate foods resulted in considerably increased de novo lipogenesis (DNL) in the liver within just 9 d (12).…”
Section: Introductionmentioning
confidence: 99%
“…The interference effect 24 h after LPS induction was stronger than that 48 h after LPS induction, while the pSUPER empty plasmid had no effect. IL-6 and -8 expression is activated through the nuclear factor κ-light-chain-enhancer of activated B cell pathway, by IL-1β and TNF-α (35). In the present study, to investigate whether pSUPER-IL-6 transfection exerted a non-specific effect and affected IL-8 secretion, IL-8 protein levels were also assessed following transfection.…”
Section: Discussionmentioning
confidence: 94%